GREEN BANKING, GOOD CORPORATE GOVERNANCE DAN FIRM SIZE : DAMPAKNYA TERHADAP PROFITABILITAS PERBANKAN (2019-2023) - Nabila Zulfa Kayana; Nur Isna Inayati; Hardiyanto Wibowo; Novi Dirgantari (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to analyze the effect of green banking, good corporate governance (GCG), and firmsize on the profitability of conventional banks in Indonesia for the 2019–2023 period. GCG is measured based on governance indicators disclosed in annual reports. Profitability is proxied by Return on Assets (ROA). This research uses a quantitative approach with secondary data from the annual reports of banks listed on the Indonesia Stock Exchange (IDX). The sample was selected using purposive sampling. A total of 200 observations were obtained from 40 banks over five years. Data were analyzed using panel data regression. Model selection was carried out through Chow, Lagrange Multiplier (LM), and Hausman tests. The best model used is the Random Effect Model (REM) with robust standard error to address heteroscedasticity and autocorrelation issues. The results show that green banking and GCG have no significant effect on profitability. In contrast, firmsize has a positive and significant effect. This finding indicates that firm scale is more dominant in determining financial performance than the implementation of green banking or governance practices. The results imply that banks need to review sustainability and governance strategies so they are not merely symbolic but have a real impact on profitability.